2015
DOI: 10.1016/j.celrep.2015.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Differential Connexin Function Enhances Self-Renewal in Glioblastoma

Abstract: SUMMARY The coordination of complex tumor processes requires cells to rapidly modify their phenotype and is achieved by direct cell-cell communication through gap junction channels composed of connexins. Previous reports have suggested that gap junctions are tumor suppressive based on connexin43 (Cx43), but this does not take into account differences in connexin-mediated ion selectivity and intercellular communication rate that drive gap junction diversity. We find that glioblastoma cancer stem cells (CSCs) po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(125 citation statements)
references
References 55 publications
3
114
0
Order By: Relevance
“…In contrast, Cx32 was localized to the cytoplasm and was suggested to enhance the CSC self-renewal in Huh7 hepatoma cells 181 raising the question as to whether connexin isoform specificity is critical. Intriguingly, glioblastoma CSCs were shown to express Cx46 whereas non-CSCs expressed Cx43 182 suggesting specific channel permeability properties regulate self-renewal versus differentiation. This result also has implications for the therapeutic concept of the “bystander effect”, where spread of either death or survival signals between neighbouring cells may occur via functional GJIC as discussed in detail below.…”
Section: Reassessing Connexins In Cancermentioning
confidence: 99%
“…In contrast, Cx32 was localized to the cytoplasm and was suggested to enhance the CSC self-renewal in Huh7 hepatoma cells 181 raising the question as to whether connexin isoform specificity is critical. Intriguingly, glioblastoma CSCs were shown to express Cx46 whereas non-CSCs expressed Cx43 182 suggesting specific channel permeability properties regulate self-renewal versus differentiation. This result also has implications for the therapeutic concept of the “bystander effect”, where spread of either death or survival signals between neighbouring cells may occur via functional GJIC as discussed in detail below.…”
Section: Reassessing Connexins In Cancermentioning
confidence: 99%
“…In addition to the changes in protein function and gene transcription described above, blocking Cav3.2 might also influence GSC function by affecting resting membrane potential. In fact, recently published research has shown that brain tumor stem cells have elevated resting membrane potential that is regulated by connexins and EAG2 potassium channels to influence these cells' malignant functions (49, 50). …”
Section: Discussionmentioning
confidence: 99%
“…This variability in Cx43 expression levels suggests that this GJ protein plays divergent roles in GBMs. This may also extend to differential expression of other connexins by GBM cells [24]. Lathia and colleagues reported that the ratio of Cx46 to Cx43 was elevated in GSCs, whereas following differentiation into non-CSC GBM cells, Cx46 is reduced and Cx43 is increased.…”
Section: Connexin43 Expression In Malignant Gliomamentioning
confidence: 99%